Psychometric Evaluation of the Persian Version of the Childbirth Experience Questionnaire (CEQ) - Kazemi, Samiyeh (Biomed Res Int, 2020)
Women's childbirth experience is an outcome indicator for evaluating maternity care. This study evaluated the psychometric properties of the Persian version of the Childbirth Experience Questionnaire (P-CEQ). The study recruited two hundred and fifty primiparous postpartum women in the 1-3 months following birth from one private and three public hospitals in Mazandaran province, Iran. First, face validity and content validity were evaluated. Moreover, confirmatory factor analysis (CFA) was conducted, and discriminant validity was assessed by applying the known-groups method. Intraclass correlation coefficient (ICC) was measured to confirm the stability and Cronbach's alpha to confirm the internal consistency. CFA also confirmed the values of fit indices (RMSEA = 0.05, SRMSR = 0.06, CFI >0.93, χ(2)/df = 1.80). ICC was 0.88 and Cronbach's alpha for all items was 0.85. Furthermore, discriminant validity of the P-CEQ was approved given that it effectively differentiated women whose stay in the labor unit exceeded twelve hours from those with a shorter stay. The P-CEQ questionnaire is a valid and reliable tool for assessing childbirth experiences. It is an easy-to-use questionnaire that can be used for evaluating quality of care in terms of women's childbirth experience. It can be used in maternity services that aim to improve quality of care during labor and childbirth.